2021
DOI: 10.3389/fphar.2021.637904
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in Injection-Based Therapy for Thumb-Base Osteoarthritis: Where Are We and where Are We Going?

Abstract: Thumb-base osteoarthritis (TBOA) is a common condition, mostly affecting post-menopausal women, often inducing a significant impact on quality of life and hand functionality. Despite its high prevalence and disability, the therapeutic options in TBOA are still limited and few have been investigated. Among the pharmacological strategies for TBOA management, it would be worthwhile to mention the injection-based therapy. Unfortunately, its efficacy is still the subject of debate. Indeed, the 2018 update of the Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 72 publications
(120 reference statements)
0
8
0
3
Order By: Relevance
“…This institute focused on the management of non-drug, drug and surgical treatment of OA. Their recent research demonstrated that HA not only could be applied to KOA and hip osteoarthritis (HOA), but also could be used to thumb-base osteoarthritis (TBOA) ( Tenti et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This institute focused on the management of non-drug, drug and surgical treatment of OA. Their recent research demonstrated that HA not only could be applied to KOA and hip osteoarthritis (HOA), but also could be used to thumb-base osteoarthritis (TBOA) ( Tenti et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…HA enables OA to recover the rheological nature of synovial fluid, thereby relieving the injury and improving functionality, but its efficacy remains controversial. GC injections (rather than HA intra-articular injections) are often recommended for knee OA and thumb-base OA (7,39,40). Other methods of intra-articular treatment, including small-molecule drugs, stem-cell therapy, and growth-factor therapy, are still under clinical development.…”
Section: Discussionmentioning
confidence: 99%
“…However, intra-articular, base of thumb injections of hyaluronic acid [58,59] (for chronic management) and corticosteroid [59][60][61] (for acute phase management) appear to be promising approaches and could be conditionally proposed (though with the caveat that further efficacy and safety data are required).…”
Section: Intra-articular Injectionsmentioning
confidence: 99%